Determinants of Ethical Decision Making: The Relationship of the Perceived Organizational Environment - Sims, Randi L. (Journal of business ethics, 1999)
This study attempts to help explain the ethical decision making of individual employees by determining how the perceived organizational environment is related to that decision. A self- administered questionnaire design was used for gathering data in this study with a sample size of 245 full-time employees. Perceived supervisor expectation, formal policies, and informal policies were used to assess the expressed ethical decision of the respondents. The findings indicate that the perceived organizational environment is significantly related to the ethical decision of the respondent.